Effect of surface properties on momentum transfer to targets impacted by high-velocity sand slugs. (May 2017) - Goel, A.; Uth, T.; Wadley, H.N.G.; Deshpande, V.S.
Highlights: Effect of surface properties on momentum transfer quantified. Demonstrated that inclined impacts are sensitive to surface type. The study clarifies the need to include particle shape in discrete element models. Abstract: The response of dry and water saturated sand slugs impacting normally oriented and inclined rigid-stationary targets with four different surface coatings is measured with an emphasis on the quantification of the momentum transmitted from the slugs into the targets. The targets were coated with Alumina, PTFE, Aluminium or sand-paper layers in order to investigate the effect of varying surface hardness and surface roughness. In all the cases, the fraction of the slug momentum transferred into the target was equal for dry and water saturated sand slugs and also independent of the slug velocity over the range 73 m s − 1 − 137 m s − 1 that is investigated here. For normal impacts, the surface coatings had no measurable influence on the momentum transfer into the targets and this was attributed to the symmetry of the impact event. However, the break of symmetry in the inclined impact cases resulted in two non-zero components of the net transmitted momentum into the targets and a strong influence of the surface coatings. This is attributed to friction between the sand particles and the target surface with the resultant transmitted momentum increasing in the order Alumina to PTFE to Aluminium to sand-paper surface coatings. In all cases, the transmitted momentum was less than the corresponding value under normal impact. Coupled discrete particle/Lagrangian simulations of these experiments with the sand particles modelled as spheres captured the normal impact measurements with a high degree of fidelity. However, the simulations underestimated the transmitted momentum for the inclined impacts especially for the rough surface coatings such as the sand-paper: increasing the friction coefficient between the particles and the target in the simulations did not improve the predictions. We demonstrate that this discrepancy is due to the spherical particle assumption: in the experiments the sand particles are sub-spherical and this reduces the tendency of particles to roll on the target surface and thereby increases frictional interactions. Increasing the radius of gyration of particles decreased the discrepancy between the measurements and the predictions but yet could not accurately predict all components of the transmitted momentum. Most numerical calculations tend to use spherical particles to represent the impacting granular media. However, this study demonstrates the need to appropriately parameterise particle shape in such discrete particle calculations to accurately capture the granular media/structure interactions.